2015
DOI: 10.1063/1.4906198
|View full text |Cite
|
Sign up to set email alerts
|

Influence of epitaxial strain on elastocaloric effect in ferroelectric thin films

Abstract: Articles you may be interested inEnhanced microwave dielectric tunability of Ba0.5Sr0.5TiO3 thin films grown with reduced strain on DyScO3 substrates by three-step technique

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 49 publications
(81 reference statements)
1
18
0
Order By: Relevance
“… and in several materials including ferroelectrics and antiferroelectrics. Phenomenological calculations on BaTiO 3 ‐based capacitors and thin films by Liu et al . yield inverse elastocaloric responses under compressive stress (below certain critical magnitude) applied along [001] to the tetragonal phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… and in several materials including ferroelectrics and antiferroelectrics. Phenomenological calculations on BaTiO 3 ‐based capacitors and thin films by Liu et al . yield inverse elastocaloric responses under compressive stress (below certain critical magnitude) applied along [001] to the tetragonal phase.…”
Section: Discussionmentioning
confidence: 99%
“…The authors proposed the caloric cycle concept of combining the tensile and appropriate compressive stress to take advantage of conventional and inverse elastocaloric effect similar to that explained in Section 4.3 . Furthermore, they reported that the elastocaloric response depends crucially on epitaxial strain …”
Section: Discussionmentioning
confidence: 99%
“…Multicaloric effect may also lead to search for hitherto unobserved caloric effect in ferroics 5 (e.g., elastocaloric effects in ferroelectrics 18,20,60 ) or tuning and optimizing of one single caloric effect in multiferroic materials by using a non-conjugated field (e.g., electrocaloric effect with stress 21 ). Elastocaloric properties in bulk 20,60 and thin films 18,61 ferroelectrics were predicted to be remarkable and comparable with those of martensites, 62,63 expanding the elastocaloric family. Interestingly, the mechanism of elastocaloric effect in thin films purely stems from the continuous changes of the strain, which differs from that in shape-memory alloys 3 and ferroelectric bulk.…”
Section: 3mentioning
confidence: 99%
“…The stimulus-mediated caloric effect has attracted much more attention since the additional stimulus applied on the samples may help to optimize the caloric properties such as the tuning of phase transition temperature (thus the working temperature) and to modify the largest caloric response. [24][25][26][27]31] A typical result is shown in Fig. 4.…”
Section: Insights Into the Multicaloric Effect In Normal Ferroelectricsmentioning
confidence: 99%
“…[6] Among the ferroic materials ferroelectrics can be good potential candidates for developing multicaloric effect, due to the fact that the phase transition in ferroelectrics can be triggered by electric field, uniaxial stress and hydrostatic pressure. [7] According to the literature, individual caloric effects such as electrocaloric, [8][9][10][11][12][13][14][15][16][17][18][19][20] elastocaloric [21][22][23][24][25][26][27][28] and barocaloric [28][29][30][31][32][33] scenarios have all been reported in ferroelectric materials. In this context only a few theoretical studies have been published to understand the multicaloric effect in ferroelectric bulk and thin films driven by simultaneous application of electric and mechanical fields.…”
Section: Introductionmentioning
confidence: 99%